Synthesis and characterisation of the first three-dimensional mixed-metal-center inorganic-organic hybrid framework with N-(phosphonomethyl)iminodiacetate - Paz, Filipe A. Almeida (2004)
Using crystal engineering concepts, the first three-dimensional (3D) mixed-metal-centre inorganic-organic hybrid frameworks incorporating N-(phosphonomethyl)iminodiacetate (pmida4−) were synthesised under mild hydrothermal conditions (100 °C) and characterised structurally. The crystal structures, obtained by the displacement of the coordinated water molecules in [Co2V2O2(pmida)2(H2O)10]·2(H2O) (1) [P21/c monoclinic space group, Z = 2, a = 9.996(2)A° , b = 14.854(3)A° , c = 10.781(2)A° , β = 110.90(3)° and V = 1495.5(5)A° 3] by the rod-like bridging 4,4 -bipyridine (4,4 - bpy) ligand — [CdVO(pmida)(4,4 -bpy)(H2O)2]·(4,4 - bpy)0.5·H2O (2) and [CoVO(pmida)(4,4 -bpy)(H2O)2]·(4,4 - bpy)0.5 (3) — are isostructural and were also determined in the P21/c monoclinic space group (Z = 4) by single-crystal Xray diffraction studies at low temperature (180 K): for 2, a = 9.1267(18)A° , b = 17.610(4)A° , c = 15.361(3)A° , β = 93.06(3)° and V = 2465.3(9)A° 3; for 3, a = 8.7734(18)A° , b = 17.264(4)A° , c = 15.507(3)A° , β = 93.94(3)° and V = 2343.2(8)A° 3. All the crystal structures contain centrosymmetric dimeric [V2O2(pmida)2]4− units connected to neighbouring M2+ cations (Cd2+ for 2, and Co2+ for 1 and 3) through the phosphonate group. In 2 and 3, extended two-dimensional [MVO(pmida)( H2O)2]n layers are formed, with the 4,4 -bpy molecules acting as pillars between adjacent layers, leading to porous 3D supramolecular structures, [MVO(pmida)(4,4 - bpy)(H2O)2] , with a topology resembling that of the NbO net.